Determining the risk-free rate for applying the CAPM in the brazilian market (Revista Brasileira de Contabilidade e Gestão, 2014)
The adaptation of CAPM (Capital Asset Pricing Model) to Brazilian market has been subject for several academic papers. One of the aspects related to the subject refers to the parameterization of the risk-free rate (Rf), usually oscillating in the literature between the Poupança Yield, the Selic rate and the yield from US treasury bonds. The following paper aimed to discover which of these constructs has the better fit to the CAPM’s risk free rate in Brazil. Basing on the flight to quality phenomena, we compared the behavior of Ibovespa with the behavior of these constructs. The conclusion is that, although all presented significant correlation with Ibovespa, the quality to explain the Ibovespa performance was better for the US treasury bonds, classifying it as the recommended asset to the risk-free rate in Brazil.
Keywords: risk-free rate; CAPM; risk aversion; flight to quality